WATCHING TED TALK ON STUDENTS’ SPEAKING SKILL - Harahap, Sartika Dewi; Syauqi, Muhammad Habibi; Azizah, Fani; Khotimah, Aulia Nur (JR-ELT (Journal of Research in English Language Teaching), 2025)
This study aims to explore students’ perceptions of watching TED Talks as an authentic medium for developing English speaking skills. The research employed a qualitative approach involving first-semester students of the English Education Department at STAIN Mandailing Natal during the odd semester of the 2025 academic year. Twenty students were selected through purposive sampling based on preliminary observations indicating difficulties in speaking English. Data were collected through semi-structured interviews and classroom observations to gain in-depth insights into students’ experiences and perceptions. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings reveal that students generally perceive TED Talks positively as an effective learning medium that enhances motivation, confidence, and awareness of speaking components. Exposure to TED Talks helps students develop greater awareness of pronunciation, grammar usage, fluency, and vocabulary in authentic communicative contexts. Although some students initially feel intimidated by the speakers’ proficiency, repeated exposure gradually reduces anxiety and encourages reflective and independent learning.